Tumor bed proton irradiation in young children with localized medulloblastoma. Issue 12 (12th September 2019) - Grewal, Amardeep S.; Li, Yimei; Fisher, Michael J.; Minturn, Jane; Paltin, Iris; Belasco, Jean; Phillips, Peter; Kang, Tammy; Lustig, Robert A.; Hill‐Kayser, Christine
Abstract: Background: Radiotherapy is often deferred in very young children with medulloblastoma, in favor of more intense chemotherapy and stem cell rescue; however, posterior fossa radiation has been shown to improve overall survival (OS) and event‐free survival compared with adjuvant chemotherapy alone. This study was performed to assess the OS, recurrence‐free survival (RFS), patterns of failure, and clinical toxicity for children aged five and under who received focal proton radiation to the tumor bed alone. Procedure: From 2010 to 2017, 14 patients with newly diagnosed medulloblastoma at one institution received tumor bed irradiation following surgery and chemotherapy. The median age of the patients was 40 months (range, 10.9‐62.9 months). Results: With a median follow‐up of 54 months, four patients relapsed: three within the central nervous system (CNS) outside of the posterior fossa, and one within the tumor bed after subtotal resection. All relapses occurred within 28 months after the completion of radiation therapy. Five‐year OS and RFS for this cohort of patients were 84% (95% CI, 48%‐96%) and 70% (95% CI, 38%‐88%), respectively. One patient experienced significant tumor regrowth soon after completion of radiation, autopsy showed viable tumor and necrosis near and within the brainstem, with relation to radiation unknown; however, no other acute clinical toxicities greater than grade 2 were observed in this group of patients. In the nine patients with available performance status follow‐up, no significant changes in Lansky performance status were observed. Conclusions: Five‐year OS and RFS following tumor bed irradiation in young children with medulloblastoma appear to be improved compared with other studies that forego the use of radiation therapy in this patient population. This approach should be further investigated in young children with medulloblastoma.